Classifying Water Quality of Wando and Tamari According to the Characterization of H2O Stable Isotope and Ionized Type in the Middle and Lower Kiso River* - Matsumoto, Yoshitaka; Nakanishi, Genki; Sagawa, Shiro; Inoue, Takanobu; Yokota, Kuriko (Journal of Engineering and Technological Sciences, 2015)
Wando and tamari are water bodies in the floodplain of a river and play an important role in maintaining valuable ecosystems. There are over 100 wando and tamari in the middle and lower basin of the Kiso River. An Acheilognathus longipinnis, Itasenpara Bitterling, which is designated as an endangered species, has been identified in these areas. The habitat of these valuable wando and tamari species is endangered by the development of large land plants around these reservoirs caused by river dredging for flood protection. Therefore, it is essential to collect detailed data about the habitat, hydraulic water flow, physical structures and landscape in order to preserve this species, but so far little attention has been given to water quality. The purpose of our research was to classify the water quality of wando and tamari water, especially ions, and to determine the water type based on its origin. Samples were collected at 10 wando sites and 15 tamari sites from August 2011 to February 2013 along the Kiso River. As our analysis by trilinear diagram shows, the waters of wando and tamari almost all belong to the category of Type I (Ca-HCO3), which forms in shallow aquifers. The two reservoirs that do not belong to Type I are presumably contaminated by drainage water from human activities.